Novel microbial consortia facilitate metalliferous immobilization in non-ferrous metal(loid)s contaminated smelter soil: Efficiency and mechanisms. (15th November 2022) - Li, Miaomiao; Yao, Jun; Sunahara, Geoffrey; Hawari, Jalal; Duran, Robert; Liu, Jianli; Liu, Bang; Cao, Ying; Pang, Wancheng; Li, Hao; Li, Yangquan; Ruan, Zhiyong
Abstract: Exposure to toxic metals from nonferrous metal(loid) smelter soils can pose serious threats to the surrounding ecosystems, crop production, and human health. Bioremediation using microorganisms is a promising strategy for treating metal(loid)-contaminated soils. Here, a native microbial consortium with sulfate-reducing function (SRB1) enriched from smelter soils can tolerate exposures to mixtures of heavy metal(loid)s (e.g., As and Pb) or various organic flotation reagents (e.g., ethylthionocarbamate). The addition of Fe 2+ greatly increased As 3+ immobilization compared to treatment without Fe 2+, with the immobilization efficiencies of 81.0% and 58.9%, respectively. Scanning electronic microscopy-energy dispersive spectroscopy, X-ray diffraction, and X-ray photoelectron spectroscopy confirmed that the As 3+ immobilizing activity was related to the formation of arsenic sulfides (AsS, As4 S4, and As2 S3 ) and sorption/co-precipitation of pyrite (FeS2 ). High-throughput 16S rRNA gene sequencing of SRB1 suggests that members of Clostridium, Desulfosporosinus, and Desulfovibrio genera play an important role in maintaining and stabilizing As 3+ immobilization activity. Metal(loid)s immobilizing activity of SRB1 was not observed at high and toxic total exposure concentrations (220–1181 mg As/kg or 63–222 mg Pb/kg). However, at lower concentrations, SRB1 treatment decreased bioavailable fractions of As (9.0%) and Pb (28.6%) compared to without treatment. Results indicate that enriched native SRB1 consortia exhibited metal(loid) transformation capacities under non-toxic concentrations of metal(loid)s for future bioremediation strategies to decrease mixed metal(loid)s exposure from smelter polluted soils. Graphical abstract: Image 1 Highlights: Sulfate-reducing bacteria consortia (SRB1) can tolerate multi-metal(loid)s and organic flotation reagents. Arsenic bio-immobilization involves formation of arsenic sulfides and sorption/co-precipitation of pyrite. Bioavailable metal(loid)s were decreased by SRB1 in metal-contaminated smelter soils.